Complex systems : École d'été de Physique des Houches, session LXXXV, 3-28 July 2006 ; École thématique du CNRS - Bouchaud, Jean-Philippe, 1962-; Mezard, Marc; Dalibard, J. (Elsevier, 2007)
There has been recently some interdisciplinary convergence on a number of precise topics which can be considered as prototypes of complex systems. This convergence is best appreciated at the level of the techniques needed to deal with these systems, which include: 1) A domain of research around a multiple point where statistical physics, information theory, algorithmic computer science, and more theoretical (probabilistic) computer science meet: this covers some aspects of error correcting codes, stochastic optimization algorithms, typical case complexity and phase transitions, constr.